Pengaruh Model Pembelajaran Realistic Mathematics Education dan Motivasi Belajar Terhadap Hasil Belajar Peserta Didik pada Materi Pecahan - Khotimah, Khusnul; Riyadi, Riyadi; Supianto, Supianto (Universitas Sebelas Maret, 2026)
This research has three objectives: (1) to determine the effect of the application of the Realistic Mathematics Education (RME) learning model and the application of conventional learning models on students' mathematics learning outcomes on fraction materials, (2) to determine the effect of students with high learning motivation and low learning motivation on students' mathematics learning outcomes on fraction materials, and (3) to determine the interaction between the Realistic Mathematics Education (RME) learning model and learning motivation on students' learning outcomes on fraction materials. The research conducted was quantitative research with a quasi-experimental method. Fourth grade students of SD Negeri se-Dabin V Tawangsari District became the population of this study. There are two elementary schools that became the research sample taken by cluster sampling technique. Data collection was carried out using a learning outcome test and a learning motivation questionnaire. The data in this study were analyzed using the two-way anava technique with unequal cells, which was preceded by prerequisite analysis tests such as normality, homogeneity, and balance tests. The results of the study obtained that: F(A) count = 82.61 > 4.28 = F(A) table, then H0 is rejected. Furthermore, F(B) count = 13.92 > 4.28 = F(B) table, then H0 is rejected. Meanwhile, F(AB) calculated = 2.47 > 4.28 = F(AB) table, then H0 is accepted. Referring to the data that has been analyzed, it can be concluded that: 1) there are differences in the mathematics learning outcomes of students who are given learning with the Realistic Mathematics Education model with students who are given learning with conventional learning models; 2) there are differences in mathematics learning outcomes in students who have high learning motivation with students who have low learning motivation; 3) shows no interaction between learning models and learning motivation on students' mathematics learning outcomes.